KONSEP MAHAR SYAR'I DALAM PERSPEKTIF HADIS: (Kajian Ma'anil Hadis) - Nurmansyah, Ihsan (Al-Bayan: Jurnal Ilmu al-Qur'an dan Hadist, 2022)
This paper discusses the issue of one of the syar'i dowries in the form of memorizing the Qur'an which is increasingly used by married couples as a dowry in their marriage. In response to this, there are differences of opinion, some are pro and some are contra, of course it is very much influenced by the understanding of the hadith text. Therefore, it is very important to review the understanding of the hadith text by using the ma'anil hadith study. The conclusion is that mahar syar'i, in the form of teaching the Qur'an, is better understood than memorizing the Qur'an, because dowry should be something that can be judged. During the time of the Prophet Muhammad, various forms of dowry were carried out in honor of the wife by adjusting men's abilities, including 50 dirhams worth of household furniture, a gold seed, armor, freeing slaves and a pair of sandals. Of the various variations of the dowry, all of them have value and can be useful for the bride so that the form or amount of the dowry is very flexible according to the appropriateness of society and men's abilities. Thus, mahar syar'i is not only in the form of reading or memorizing the Qur'an.